PENGEMBANGAN NILAI-NILAI KEMANUSIAAN BERBASIS MULTIPLE INTELLIGENCES - Suri, Dharlinda (Lembaga Penelitian STKIP PGRI Bandar Lampung, 2014)
Human values concerning the rules that apply in considering whether the practices relating to humanity has been implemented, based on fairness and equality. Therefore, humanitarian values include; Respect for keagamanan religious affiliations, Respect keragamanan ethnic tribes and nations against keragamanan, Awards keragamanan culture on individual potential, keragamanan Respect for gender equality before the law, equality Respect in obtaining a sense of security, Respect for equality in obtaining educational services, Respect for freedom of speech.